1991
DOI: 10.1080/14640749108401276
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Learning in Maze Discriminations

Abstract: In Experiment 1, rats were trained on a discrimination between rubber- and sandpaper-covered arms of a maze after one group had been pre-exposed to these intra-maze cues. Pre-exposure facilitated subsequent discrimination learning, unless the discrimination was made easier by adding further discriminative stimuli, when it now significantly retarded learning. In Experiment 2, rats were trained on an extra-maze spatial discrimination, again after one group, but not another, had been pre-exposed to the extra-maze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 8 publications
4
45
0
Order By: Relevance
“…Oswalt, 1972), and that if this requirement is not met then pre-exposure can instead lead to a deficit in learning (e.g. Trobalon, Sansa, Chamizo and Mackintosh, 1991). All these results (which are predicted by MKM) suggest that there is an intimate relationship between latent inhibition on the one hand, and perceptual learning on the other.…”
Section: Problem Domainsupporting
confidence: 51%
“…Oswalt, 1972), and that if this requirement is not met then pre-exposure can instead lead to a deficit in learning (e.g. Trobalon, Sansa, Chamizo and Mackintosh, 1991). All these results (which are predicted by MKM) suggest that there is an intimate relationship between latent inhibition on the one hand, and perceptual learning on the other.…”
Section: Problem Domainsupporting
confidence: 51%
“…Bulut and Altman (1974) demonstrated that pups as young as PND6 were able to make position and tactile discriminations. Other experimenters have shown successful discrimination using different texture manipulations (sandpaper, rubber, rough tile flooring) with both young and mature rats (Bulut & Altman, 1974;Trobalon, Chamizo, & Mackintosh, 1992;Trobalon, Sansa, Chamizo, & Mackintosh, 1991). Data from our lab (Brown, Pagani, & Stanton, 2004, Experiment 2) indicate that the mesh used in the present experiment is sufficiently salient to be used as a discriminative cue in PND30 rats.…”
Section: Discussionmentioning
confidence: 47%
“…The evidence on this matter is decidedly mixed. Although it has sometimes been found that perceptual learning is attenuated by a change of context (Trobalon, Chamizo, & Mackintosh, 1992), other experiments have demonstrated that the effect can survive (e.g., Gibson & Walk, 1956), or even be enhanced by (Channell & Hall, 1981;Hall & Channell, 1983), a context change. For the latter cases at least, it seems necessary to assume that the processes that produce the perceptual learning effect do not depend on within-stimulus associations of the sort postulated by McLaren et aI.…”
Section: Resultsmentioning
confidence: 99%